Javier Velaza Frías, Léxico de inscripciones ibéricas (1976-1989), Barcelona, Universitat de Barcelona, 1991, 204 pp. ISBN 84-7875-556-X (Minerva. Revista de Filología Clásica, 2019)
Reseña de Javier Velaza Frías, Léxico de inscripciones ibéricas (1976-1989), Barcelona, Universitat de Barcelona, 1991, 204 pp. ISBN 84-7875-556-X